2007
DOI: 10.1097/01.rlu.0000257334.65253.cc
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography for Predicting Malignancy of Sinonasal Inverted Papilloma

Abstract: The SUVmax value of a sinonasal tumor can warn the surgeon of the probability of an associated malignancy, even when preoperative biopsy demonstrates a purely benign papilloma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 10 publications
0
34
0
Order By: Relevance
“…Glycolytic activity has been shown to be increased in inverted papilloma and low grade squamous cell carcinoma on Fluorine-18 fluorodeoxygluxose positron emission tomography (FDG PET) imaging [12].…”
Section: Discussionmentioning
confidence: 99%
“…Glycolytic activity has been shown to be increased in inverted papilloma and low grade squamous cell carcinoma on Fluorine-18 fluorodeoxygluxose positron emission tomography (FDG PET) imaging [12].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a 2015 study containing 27 patients demonstrated that 18FDG-PET/CT is able to distinguish polyposis, SIP and SCC by distinct standardized uptake value (SUV max ) values (45). Shojaku et al (46) confirmed that higher SIP SUV max values may indicate the probability of an associated malignancy, even when preoperative biopsy indicates a benign papilloma. By contrast, another study containing 8 patients reported a wide discrepancy between MRI and PET/CT findings (47).…”
Section: Clinical Prevention For the Recurrence Of Sipmentioning
confidence: 82%
“…[1,4] It is known as a histologically benign tumor, but it has certain malignant features including high tendency to recur, local aggressiveness and multifocal character. [5] Co-existence with SCC was reported at a rate ranging from 5.5% to 27% [2] while transformation into SCC was reported at a rate varying from 2% to 53%. [4] Although many studies about the mechanisms of growth and malignant transformation of IP have been carried out, these issues have not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that there is a strong correlation between increased tumoral uptake of FDG and the number of live tumor cells. [3] Although there are studies indicating increased uptake of FDG in the coexistence of IP and SCC, [2] limited data are available about FDG uptake in patients with sole IP. [3,4] The primary aim of this study is to determine whether there is a difference in terms of FDG uptake between IP and SCC, which require therapeutic approaches different from each other.…”
mentioning
confidence: 99%
See 1 more Smart Citation